2015
DOI: 10.1007/s11356-015-4342-9
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-anatomical and growth alterations induced by arsenic in Cajanus cajan (L.) DC (Fabaceae)

Abstract: Arsenic (As) is a toxic element to most organisms. Studies investigating anatomic alterations due to As exposure in plants are scarce but of utmost importance to the establishment of environmental biomonitoring techniques. So, this study aimed to investigate the effects of As on the development and initial root growth in Cajanus cajan (Fabaceae), characterize and quantify the possible damages, evaluate genotoxic effects, and identify structural markers to be used in environmental bioindication. Plants were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Exposure of Cajanus cajan seedlings to 20 M arsenate led to an increase in density of root cortex cells as well as a reduction in the percentage of intercellular spaces (Pita-Barbosa et al 2015). In leaves of A. thaliana exposed to As, the spongy parenchyma was the most severely affected, which in turn is likely to interfere in respiration and photosynthesis via reductions in mesophyll conductance.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of Cajanus cajan seedlings to 20 M arsenate led to an increase in density of root cortex cells as well as a reduction in the percentage of intercellular spaces (Pita-Barbosa et al 2015). In leaves of A. thaliana exposed to As, the spongy parenchyma was the most severely affected, which in turn is likely to interfere in respiration and photosynthesis via reductions in mesophyll conductance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to length reduction, root color of treated Vicia villosa plants were brownish and darker. Root growth reduction, which was particularly prominent in lateral roots, as well as abnormal development of the root cap, occurred in Cajanus cajani plants treated with As [ 33 ].…”
Section: The Adverse Impacts Of Heavy Metals On Legumesmentioning
confidence: 99%
“…Findings reported by Ibañez et al [ 32 ] indicate that root diameter, cortex length, and vascular cylinder size in V. villosa roots treated with As (V) (25 µM) were reduced, but no significant changes were noted in samples treated with As (III) at the same concentration. Pita-Barbosa et al [ 33 ] recorded an increase in the vascular cylinder/root diameter ratio in Cajanus cajan (L.) DC roots treated with As (1.5 mg L −1 ), accompanied by a reduction in secondary xylem vessel diameter due to the negative effect of arsenic on cambium activity.…”
Section: Anatomical Basis Related To Hm Uptake and Translocation In L...mentioning
confidence: 99%
“…It is necessary to understand how plants respond to natural levels of As and other toxic elements to develop management practices for food safety and human health. Recent evidence from model plants and wellstudied crop species revealed that As reshapes the spatial configuration of roots in thale cress (Arabidopsis thaliana) (Kumar et al 2020;Piacentini et al 2020), pigeon pea (Cajanus cajan) (Pita- Barbosa et al 2015), peanut (Arachis hypogea) (Bianucci et al 2017), and rice (Oryza sativa) (Ronzan et al 2019;Wang et al 2018), among others. The presence of As exerts a profound effect on root architecture that is tightly coordinated with the detoxification machinery (Navarro et al 2022).…”
mentioning
confidence: 99%